Inovasi dalam Pelayanan Publik: Studi Kasus Implementasi E-Government di Negara-Negara Berkembang - Marsidi, Marsidi; Mulyadi, Mulyadi; Rambe, Adi Saputra; Oktalisa, Elsy (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
Innovation in public services has become one of the most important issues in developing countries. One of the latest efforts to improve the efficiency and accessibility of public services is through the implementation of E-Government. This article discusses case studies of how developing countries have adopted this innovation and tries to measure its impact in improving services to the public. With digital technology becoming more prevalent, E-Government promises to significantly change the way governments interact with their citizens, as well as increase transparency and accountability in public services. This article will review the extent to which E-Govern